The role of communication, information and education in preventing stunting among stakeholders in Abang Village, Karangasem Regency - Marhaeni, A A I N; Yuliarmi, Ni Nyoman; Primajana, Dewa Jati; Pradnyadewi, Diah; Yasa, I G W Murjana; Jayanthi, Ni Kadek Eka; Aryasthini M, Made Sinthya (Central Community Development Journal, 2024)
One of the pillars of the 5 pillars of the Grand Design for Population Development  in Indonesia is the improvement of population quality. In the effort to enhance pop- ulation quality, one of the pathways that can be taken is to reduce the prevalence of stunting in all regions of Indonesia. Data shows that the lowest stunting prevalence is in Bali Province, but among the regencies/cities within it, Karangasem Regency has the highest prevalence of stunting, making its acceleration a matter of great importance. The objectives of this community  service activity are: 1) to evaluate    the knowledge, attitudes, and practices related to stunting among young mothers, pregnant women, families with stunted children, integrated health post (Posyandu) cadres, and community leaders in Abang Village after providing Communication, Information, and Education (CIE) on caregiving, the adverse effects of stunting, demographic bonuses, and being Foster Parents for Stunted Children; 2) to enhance the roles of relevant stakeholders in the effort to prevent and reduce stunting in the village. This activity was conducted in Abang Village, Abang District, Karangasem Regency. Karangasem Regency was chosen as the location of the activity because it has the highest prevalence of stunting in Bali Province. The method of the activity involved providing CIE (Communication, Information, and Education) on stunting delivered by two speakers, a pediatrician, and an academic from a university. After the CIE, an evaluation of the Knowledge, Attitude, and Practice (KAP) of the par- ticipants was carried out, and the results were analyzed using descriptive statistics. The analysis results show: 1) knowledge, attitudes, and practices regarding stunting vary greatly among all stakeholders, where, in general, most of them have heard about stunting but do not yet understand their roles in preventing/reducing stunt- ing; 2) an increase in the roles of stakeholders in the effort to prevent and reduce stunting through improved attitudes and future practices they will engage in to prevent and reduce stunting.